Organizational Behavior in The Implementation of The Merdeka Curriculum at The Center of Excellence Vocational School in Batam City - Suaduon, Jogie; Yamin, Martinis; Widdah, Minnah El (IJELR: International Journal of Education, Language, and Religion, 2024)
The purpose of this research is to find out about the Organizational Behavior of the Center of Excellence Vocational School in Batam City in implementing the Merdeka Curriculum. The research uses a descriptive qualitative research approach. Data collection techniques were carried out using observation, interviews and documentation. Research subjects include the Principal, Deputy Principal, Head of Skills Program & Teachers. The results of this research are that in managing the Center for Excellence Vocational School program in Batam, the Principal carries out his role well, the program management process includes activities including program planning, program implementation and program evaluation. Leadership Style, Organizational Culture & Motivation influence Individual Behavior in carrying out the planned Merdeka Curriculum Program. Individual behavior can be in accordance with organizational expectations if the Leadership Style can be adaptive according to the needs of the organization, motivation is maintained, and the Organizational Culture is able to provide value for itself. If individual behavior is integrated with these values, commitment to the organization will be strong, thereby creating the best quality of education.